MO717: Prevalence and Management of Non-Valvular Atrial Fibrillation in Peritoneal Dialysis. Results of a Multicentric Survey. (3rd May 2022) - Perez-Bernat, Elisa; Cases, Aleix; Gonzalez-Rico, Miguel; Montomoli, Marco; Moncho, Francesc; Fernanda Alvarado, Maria; Solano Rivera, Camila; Emilio Sanchez-Alvarez, J.; Ortega Cerrato, Agustin; Luis Gorriz Teruel, Jose
Abstract: BACKGROUND AND AIMS: Among patients with chronic kidney disease, the incidence and prevalence of nonvalvular atrial fibrillation (NVAF) increases as renal function decreases, detecting a prevalence of up to 27% in hemodialysis patients. However, its prevalence among patients on peritoneal dialysis (PD) has been less studied. The aim of the study is to analyse the prevalence of NVAF and characteristics related to its management in PD patients older than 18 years. METHOD: An observational, cross-sectional, multicenter and retrospective study was carried out through a survey and request for variables sent through a Google questionnaire to PD units in our country. A total of 1403 patients from 30 PD units were included. RESULTS: The mean prevalence of NVAF in the study was 13.2%, median 11.7% (interquartile range: 6.1–19.4). A total of 60% of the centers had a prevalence >10%. A total of 57.6% ( n = 17) used the CHADS2 or CHAS2-VASC score to calculate the risk of stroke/thromboembolism in their patients with NVAF. A total of 43.3% ( n  = 13) do not use it. In these cases, 15.3% ( n  = 2) do not calculate it because they treat all patients with NVAF and the remaining 84.6% ( n = 11) do not use it because the cardiologist uses it and delegates it to them. Regarding the decision to start anticoagulant treatment in NVAF: in 60% of the centers ( n = 18) the cardiologist indicates anticoagulation, in 36.7% ( n = 11) the indication is made jointly (cardiologist and nephrologist) and only in 3.3% ( n = 1) the indication is made by the nephrologist. A total of 72.5% of the patients with NVAF (135/186) received anticoagulant treatment. Of these, 28 (20.7%) received direct-acting anticoagulants and 107 (79.3%) received acenocoumarol. Among direct-acting anticoagulants, the most frequent regimens were: apixaban 2.5 mg/12 h (86%), and edoxaban 30 mg/24 h (7%). A total of 5.9% (11/186) of patients with NVAF did not receive anticoagulant or antiplatelet treatment. A total of 90% of the centers ( n = 27) are familiar with the technique of percutaneous appendage closure for the treatment of NVAF, but it is not available in five of them. This technique has been performed in 17 of the patients with NVAF. CONCLUSION: The prevalence of NVAF in PD patients is high. The management of these patients is carried out mainly by cardiologists with little participation of nephrologists. Most patients receive anticoagulant treatment with coumarin drugs. The data from this analysis, as well as the limited data from the literature, indicate that an adequate format, a consensus document, as well as more data from observational studies (and especially from randomized controlled trials) are needed to adequately address this common complication in patients with DP.